Pengembangan Pendidikan Lintas Budaya dalam Konteks Indonesia - Hariani, Farida; Ahmadin, Ahmadin; Ibrahim, Ibrahim (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The development of cross-cultural education is a strategic necessity for Indonesia as a country with a high level of ethnic, religious, linguistic and cultural diversity. This study aims to analyse the concept, urgency and direction of cross-cultural education development in the context of Indonesian national education. The method used is a literature study by examining various scientific sources in the form of books, journal articles, and policy documents relevant to cross-cultural education and multicultural education. The data were analysed descriptively and qualitatively to identify the principles, forms of implementation, and challenges faced in its application. The results of the study show that cross-cultural education plays an important role in fostering tolerance, empathy, mutual respect, and the ability to interact harmoniously in a pluralistic society. The integration of cross-cultural values in the curriculum, contextual learning, and collaboration between schools, families, and communities have been proven to support the character building of students and the prevention of social conflict.